Factor Structure and Psychometric Properties of the Family Communication Scale in the Chinese Population - Guo, Ningyuan; Ho, Henry C. Y.; Wang, Man Ping; Lai, Agnes Y.; Luk, Tzu Tsun; Viswanath, Kasisomayajula; Chan, Sophia S.; Lam, Tai Hing (Frontiers in Psychology, 2021)
Purpose: To evaluate the factor structure and psychometric properties of the 10-item Family Communication Scale (FCS) in the Chinese population. Methods: Study 1 was a population-based survey (N = 687, 61.1% female; mean age [SD] 56.6 [19.1]). Study 2 was a community-based intervention (N = 1983, 76.7% female; 57.8% aged 20–59). We conducted exploratory factor analysis (EFA) in Study 1 and replicated the model by confirmatory factor analysis (CFA) in Study 2. Psychometric properties were evaluated including internal consistency, test-retest reliability, convergent and discriminant validity, and known-group validity. We identified how FCS scores differed by sociodemographic characteristics and communication methods including face to face and Information and Communication Technologies (ICTs) in Study 1. Results: EFA and CFA supported a one-factor structure. The Chinese FCS showed good internal consistency (Cronbach alpha = 0.91; McDonald’s Omega = 0.91) and was stable over one-month (intraclass correlation coefficient = 0.69, P < 0.001). Convergent validity was supported by positive correlations of FCS with the Subjective Happiness Scale, Family APGAR Scale (Adaption, Partnership, Growth, Affection, Resolve), family health, harmony, and happiness, and perceived family communication sufficiency and quality (All P < 0.001). Discriminant validity was supported by the stronger correlation of FCS with Short Form-12 Health Survey Version 2 Mental Component than that with Physical Component (P < 0.001). Higher household income, frequent face-to-face communication, and frequent use of phone calls, instant messaging, and social networking sites were associated with higher FCS scores. Conclusion: The one-factor structure of Chinese FCS can be a reliable and valid measurement of positive family communication, in the context of ICTs integration into family communication.